Asphalt concrete using foam warm mix and preparation method thereof

By using foam warm mixing technology in asphalt concrete, combined with nano foaming agent and organic viscosity-reducing temperature mixing additives, the problems of high viscosity and large energy consumption of traditional asphalt concrete are solved, and construction efficiency and material performance are significantly improved.

CN118619589BActive Publication Date: 2025-02-11NINGBO DONGXING ASPHALT PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410650343.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-02-11
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

During the construction process, traditional asphalt concrete has problems such as high viscosity, large energy consumption, fast asphalt aging and poor internal structure, which limits its construction efficiency and performance.

Method used

Using foam warm mixing technology, by adding nano foaming agent and organic viscosity-reducing temperature mixing additives to the asphalt, the viscosity of the asphalt is significantly reduced, and the internal structure is optimized to improve fluidity and construction efficiency.

Benefits of technology

It significantly reduces the viscosity and mixing temperature of asphalt concrete, improves construction efficiency, reduces energy consumption, and improves the comprehensive performance of asphalt concrete, including compressive strength, stability and durability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a method for preparing asphalt concrete using foam warm mixing, which comprises the following steps: S1: weighing aggregates by weight and heating them, and placing the heated aggregates into a preheated mixing pot for dry mixing; S2: heating the asphalt to 130-140°C, then injecting a nano foaming agent, stirring and foaming evenly for a period of time to obtain foamed asphalt; S3: spraying the nano foaming agent and an organic viscosity-reducing warm mixing additive into a mixing pot to mix with the preheated aggregates; S4: pausing the mixing, pouring in room temperature mineral powder and water, and continuing to mix until the mixture is uniform to obtain the asphalt concrete. The present invention uses a method for preparing asphalt concrete using foam warm mixing, which solves the problems of high viscosity and high mixing temperature of traditional asphalt concrete, construction difficulties, high energy consumption, rapid asphalt aging, and poor internal structure, and significantly improves the comprehensive performance of asphalt concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of asphalt concrete, and in particular to asphalt concrete using foam warm mix and a preparation method thereof. Background Art

[0002] Asphalt concrete is a commonly used paving material in road construction and maintenance, and is widely used due to its good adhesion and waterproof properties. However, traditional asphalt concrete has some limitations during construction, which are mainly manifested in the following aspects:

[0003] High viscosity problem: Traditional asphalt concrete has a high viscosity, which requires a higher temperature during construction to ensure sufficient fluidity for paving and compaction.

[0004] Energy consumption problem: In order to achieve the viscosity required for construction, traditional asphalt concrete needs to consume a lot of energy for heating, which not only increases construction costs but also puts a burden on the environment.

[0005] Asphalt aging problem: Prolonged heating at high temperature will accelerate the aging of asphalt and affect the durability and service life of asphalt concrete.

[0006] Internal structure issues: The internal structure of conventional asphalt concrete may not be uniform enough, which may affect its overall performance, including strength and durability.

[0007] Construction efficiency: Since construction needs to be carried out at higher temperatures, this limits the construction flexibility of asphalt concrete under different climatic conditions, especially in low temperature environments.

[0008] In view of the above challenges, the road engineering industry urgently needs a new asphalt concrete preparation method that can reduce construction temperature, reduce energy consumption, and improve construction efficiency without sacrificing performance or taking into account performance improvement. The present invention came into being in this context, aiming to solve the problems existing in the prior art through innovative foam warm mix technology and promote the advancement of asphalt concrete material technology. Summary of the invention

[0009] In view of the above shortcomings of the prior art, the present invention provides an asphalt concrete using foam warm mix to solve the problems of high viscosity and high mixing temperature of traditional asphalt concrete, such as difficult construction, high energy consumption, rapid asphalt aging and poor internal structure, so as to significantly improve the comprehensive performance of asphalt concrete.

[0010] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0011] A method for preparing asphalt concrete using foam warm mix, the preparation method comprising the following steps:

[0012] S1: Weigh the aggregate by weight and heat it, put the heated aggregate into the preheated mixing pot for dry mixing, and control the dry mixing temperature to 125-145°C;

[0013] S2: heating the asphalt to 130-140°C, then injecting the nano foaming agent, stirring evenly and foaming for a period of time to obtain foamed asphalt;

[0014] S3: spraying the foamed asphalt and the organic viscosity-reducing warm mix additive obtained in step S2 into the mixing pot of step S1 and mixing with the preheated aggregate;

[0015] S4: Pause the mixing, pour in the mineral powder and water at room temperature, and continue to mix until the mixture is uniform to obtain the asphalt concrete.

[0016] As a preferred technical solution, the aggregate is composed of at least one coarse aggregate and at least one fine aggregate gradation.

[0017] As a preferred technical solution, in step S1, at least one fiber material selected from the group consisting of glass fiber, carbon fiber, basalt fiber and aramid fiber is added to the aggregate.

[0018] As a preferred technical solution, the nano foaming agent is nano molecular sieve loaded azodicarbonamide (ADCA), which is uniformly mixed with nano zinc oxide after the nano molecular sieve after acid solution pretreatment and the alkaline solution of azodicarbonamide stirring reaction. The nano foaming agent of the present invention can generate a large number of tiny and stable bubbles in asphalt quickly and evenly, and the generation of these bubbles not only significantly reduces the viscosity of asphalt, but also greatly improves the fluidity of asphalt concrete, making it easier to lay and compact during construction, thereby improving construction efficiency. More importantly, through the foaming effect of nano foaming agent in nano pore size, the volume of asphalt is reasonably and effectively expanded, which can not only more closely fill the gap between aggregates, reduce the content of free asphalt, but also avoid excessive expansion to bring about the deterioration of the mechanical properties of asphalt concrete. This structural optimization not only enhances the interfacial bonding force between asphalt and aggregate, makes asphalt concrete more tight and firm, and then improves its stability, so that it shows stronger resistance when facing traffic load and natural environment changes. In addition, the zinc oxide loaded by nano molecular sieve effectively reduces the decomposition temperature of ADCA, not only improves the foaming efficiency, but also reduces energy consumption and production cost.

[0019] As a preferred technical solution, the organic viscosity-reducing warm mix additive is compounded from a hyperbranched polymer, polyvinyl pyrrolidone, fatty acid, and amphoteric surfactant. The introduction of the organic viscosity-reducing warm mix additive of the present invention effectively reduces the viscosity of asphalt through its unique components. This effect not only improves the fluidity and workability of asphalt concrete, making its laying and compaction processes smoother, but also enhances the interfacial bonding between asphalt and aggregate, further improving the stability and durability of asphalt concrete. In addition, by reducing the viscosity of asphalt, the additive also helps to reduce stress concentration under traffic loads, thereby improving the fatigue resistance of asphalt concrete.

[0020] As a preferred technical solution, the hyperbranched polymer is prepared by heating 2,4,6-tri(4-pyridine)1,3,5-triazine and dibromoalkane through a solvent-free method, and using the active bromine atoms of the dibromoalkane to replace the nitrogen atoms on the pyridine ring of triazine to generate pyridinium salt. The application of the hyperbranched polymer of the present invention in asphalt modification significantly improves the performance of asphalt. Its unique molecular structure and highly branched characteristics enable the hyperbranched polymer to build a dense and effective network structure in asphalt, which effectively reduces the interaction force between asphalt molecules and significantly reduces the viscosity of asphalt. More importantly, the hyperbranched polymer can also form a lubricating film on the surface of the asphalt molecules, which further reduces the viscosity of the asphalt, thereby significantly improving the fluidity of the asphalt.

[0021] Furthermore, in the present invention, by introducing a hyperbranched polymer with a pyridinium ion structure, not only the viscosity of asphalt is significantly reduced and its fluidity is improved, but also the heat resistance, stability and wetting and dispersibility of the modified asphalt are greatly improved. First, the pyridinium ion, due to its high thermal stability and the synergistic triazine structure, significantly improves the heat resistance of the modified asphalt, so that the asphalt can still maintain stable performance under high temperature environment, reducing the risk of flowing and deformation. Secondly, the strong polarity of the pyridinium ion enhances the interaction between the hyperbranched polymer and the asphalt molecules, so that the two are more closely combined, thereby greatly improving the stability and durability of the modified asphalt. Finally, the polarity of the pyridinium ion also makes it easy to form hydrogen bonds with water molecules, which greatly improves the wettability and dispersibility of the modified asphalt in water, so that the modified asphalt can be more evenly mixed with the aggregate during the preparation process, and the overall performance of the asphalt mixture is improved.

[0022] As a preferred technical solution, the dibromoalkane is at least one of 1,2-dibromoethane, 1,3-dibromopropane and 1,4-dibromobutane.

[0023] As a preferred technical solution, the fatty acid is at least one of lauric acid, myristic acid, and oleic acid. The fatty acid of the present invention has good lubricity and viscosity reduction effect. In asphalt, fatty acids can undergo esterification reaction with asphalt molecules to generate ester compounds. These ester compounds can reduce the interaction force between asphalt molecules and further reduce the viscosity of asphalt. At the same time, fatty acids can also increase the fluidity of asphalt and improve its construction performance.

[0024] As a preferred technical solution, the amphoteric surfactant is at least one of dodecyl dimethyl betaine, cocamidopropyl betaine, 2-lauryl-N-carboxymethyl-N-hydroxyethyl imidazoline and 2-alkyl-N-hydroxyethyl-N-hydroxypropyl sulfoimidazoline. The amphoteric surfactant of the present invention has the characteristics of simultaneously containing cationic and anionic groups, and can form a double electric layer structure in asphalt. This structure can reduce the electrostatic repulsion between asphalt molecules and reduce the viscosity of asphalt. The amphoteric surfactant can also adsorb with asphalt molecules to form a stable interfacial film, further reduce the viscosity of asphalt, and improve its wettability and dispersibility.

[0025] Another aspect of the present invention is to provide an asphalt concrete using foam warm mix, wherein the asphalt concrete is prepared using the asphalt concrete preparation method using foam warm mix as described above.

[0026] Beneficial effects of the present invention:

[0027] The asphalt concrete preparation method of the present invention uses the foam warm mix technology with its unique foaming mechanism and additive formula, which significantly reduces the viscosity and mixing temperature of the asphalt concrete and improves the comprehensive performance of the asphalt concrete by optimizing the internal structure.

[0028] The invention adopts the method for preparing asphalt concrete by using foam warm mix, which not only improves the construction efficiency but also reduces the energy consumption and production cost, and has broad application prospect and important promotion value in the field of road construction and maintenance. DETAILED DESCRIPTION

[0029] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0030] Example 1

[0031] This embodiment uses a method for preparing warm-mixed asphalt concrete, which includes the following steps:

[0032] S1: Weigh the aggregate by weight and heat it. The aggregate is composed of coarse aggregate (limestone crushed stone with a particle size of 9.5mm to 19mm) and fine aggregate (river sand with a fineness modulus FM of 2.5 to 2.7) mixed in a mass ratio of 50:50. Add basalt fiber to the aggregate in an amount of 0.6% of the total mass of the aggregate. Put the heated aggregate into a preheated mixing pot for dry mixing. The dry mixing temperature is controlled to be 135°C and the dry mixing time is 10 minutes.

[0033] S2: 1000g of petroleum asphalt of Road No. 70 is heated to 130°C, and then a nano foaming agent is injected; after stirring evenly, the mixture is foamed for 30 seconds to obtain foamed asphalt. The nano foaming agent is nano molecular sieve loaded with azodicarbonamide (ADCA), which is obtained by stirring 120g of nano molecular sieve pretreated with hydrochloric acid, reacting with 50g of sodium hydroxide solution of azodicarbonamide with a mass concentration of 20%, and then mixing evenly with 5g of nano zinc oxide.

[0034] S3: Spray the foamed asphalt and the organic viscosity-reducing warm mix additive obtained in step S2 into the mixing pot of step S1 at the same time and mix them with the preheated aggregate. The mass ratio of the foamed asphalt, the organic viscosity-reducing warm mix additive and the aggregate is 100:20:2000. The organic viscosity-reducing warm mix additive is composed of the following components by mass percentage: 45% hyperbranched polymer, 20% polyvinyl pyrrolidone, 18% lauric acid, and 17% dodecyl dimethyl betaine.

[0035] S4: Pause mixing, pour in room temperature limestone powder (the addition amount is 2% of the total mass of aggregate) and water with a mass of 30% of the powder, continue mixing until the mixture is uniform, mix for 5 minutes, and obtain the asphalt concrete.

[0036] The hyperbranched polymer is 2,4,6-tris(4-pyridine)1,3,5-triazine and is prepared by a solvent-free heating reaction. Specifically, at room temperature, 0.50 mol of 2,4,6-tris(4-pyridine)1,3,5-triazine and 0.75 mol of 1,2-dibromoethane are stirred and mixed evenly, heated to 48°C, and reacted for 3 hours; the reaction liquid is heated to 86°C and refluxed for 3 hours, at which time the reaction liquid gradually becomes a viscous liquid; the viscous liquid is heated to 115°C again, and the reaction is carried out by vacuum distillation for 5 hours, while the by-products are distilled out, the material is discharged, and the hyperbranched polymer crude product is obtained in a light yellow color; the crude product is washed with distilled water five times to remove a small amount of possible residual unreacted raw materials and undistilled by-products, and vacuum dried to obtain a purified hyperbranched polymer.

[0037] Example 2

[0038] This embodiment uses a method for preparing warm-mixed asphalt concrete, which includes the following steps:

[0039] S1: Weigh the aggregate by weight and heat it. The aggregate is composed of coarse aggregate (limestone crushed stone with a particle size of 9.5 mm to 19 mm) and fine aggregate (river sand with a fineness modulus FM of 2.5 to 2.7) mixed in a mass ratio of 60:40. Add glass fiber to the aggregate in an amount of 0.5% of the total mass of the aggregate. Put the heated aggregate into a preheated mixing pot for dry mixing. The dry mixing temperature is controlled to be 140°C and the dry mixing time is 10 minutes.

[0040] S2: 1000g of No. 70 road petroleum asphalt is heated to 135°C, and then a nano foaming agent is injected; after stirring evenly, the mixture is foamed for 30 seconds to obtain foamed asphalt. The nano foaming agent is the same as that in Example 1.

[0041] S3: Spray the foamed asphalt and the organic viscosity-reducing warm mix additive obtained in step S2 into the mixing pot of step S1 at the same time and mix them with the preheated aggregate. The mass ratio of the foamed asphalt, the organic viscosity-reducing warm mix additive and the aggregate is 110:23:2000. The organic viscosity-reducing warm mix additive is composed of the following components by mass percentage: 45% hyperbranched polymer, 20% polyvinyl pyrrolidone, 18% myristic acid, and 17% cocamidopropyl betaine.

[0042] S4: Pause mixing, pour in room temperature limestone powder (the addition amount is 2.5% of the total mass of aggregate) and water with a mass of 33% of the powder, continue mixing until the mixture is uniform, mix for 5 minutes, and obtain the asphalt concrete.

[0043] The hyperbranched polymer is 2,4,6-tris(4-pyridine)1,3,5-triazine and is prepared by a solvent-free heating reaction. Specifically, at room temperature, 0.50 mol of 2,4,6-tris(4-pyridine)1,3,5-triazine and 0.75 mol of 1,3-dibromopropane are stirred and mixed evenly, heated to 48°C, and reacted for 3.5 hours; the reaction liquid is heated to 88°C and refluxed for 4 hours, at which time the reaction liquid gradually becomes a viscous liquid; the viscous liquid is heated to 117°C again, and the reaction is carried out by vacuum distillation for 5 hours, while the by-products are distilled out, the material is discharged, and the hyperbranched polymer crude product is obtained in a light yellow color; the crude product is washed with distilled water five times to remove a small amount of possible residual unreacted raw materials and undistilled by-products, and vacuum dried to obtain a purified hyperbranched polymer.

[0044] Example 3

[0045] This embodiment uses a method for preparing warm-mixed asphalt concrete, which includes the following steps:

[0046] S1: Weigh the aggregate by weight and heat it. The aggregate is composed of coarse aggregate (limestone crushed stone with a particle size of 9.5 mm to 19 mm) and fine aggregate (river sand with a fineness modulus FM of 2.5 to 2.7) mixed in a mass ratio of 40:60. Aramid fiber is added to the aggregate in an amount of 0.4% of the total mass of the aggregate. The heated aggregate is placed in a preheated mixing pot for dry mixing. The dry mixing temperature is controlled to be 145°C and the dry mixing time is 10 minutes.

[0047] S2: 1000g of petroleum asphalt from No. 70 road is heated to 138°C, and then a nano foaming agent is injected; after being stirred evenly, a foaming reaction is carried out for 30 seconds to obtain foamed asphalt. The nano foaming agent is the same as that in Example 1.

[0048] S3: Spray the foamed asphalt and the organic viscosity-reducing warm mix additive obtained in step S2 into the mixing pot of step S1 at the same time and mix them with the preheated aggregate. The mass ratio of the foamed asphalt, the organic viscosity-reducing warm mix additive and the aggregate is 120:27:2000. The organic viscosity-reducing warm mix additive is composed of the following components by mass percentage: 45% hyperbranched polymer, 20% polyvinyl pyrrolidone, 18% oleic acid, and 17% 2-lauryl-N-carboxymethyl-N-hydroxyethyl imidazoline.

[0049] S4: Pause mixing, pour in room temperature limestone powder (the addition amount is 3% of the total mass of aggregate) and water with a mass of 36% of the powder, continue mixing until the mixture is uniform, mix for 5 minutes, and obtain the asphalt concrete.

[0050] The hyperbranched polymer is 2,4,6-tris(4-pyridine)1,3,5-triazine and is prepared by a solvent-free heating reaction. Specifically, at room temperature, 0.50 mol of 2,4,6-tris(4-pyridine)1,3,5-triazine and 0.75 mol of 1,4-dibromobutane are stirred and mixed evenly, heated to 48°C, and reacted for 3 hours; the reaction solution is heated to 92°C and refluxed for 4 hours, at which time the reaction solution gradually becomes a viscous liquid; the viscous liquid is heated to 120°C again, and the reaction is carried out by vacuum distillation for 6 hours, while the by-products are distilled out, the material is discharged, and the hyperbranched polymer crude product is obtained in a light yellow color; the crude product is washed with distilled water five times to remove a small amount of possible residual unreacted raw materials and undistilled by-products, and vacuum dried to obtain a purified hyperbranched polymer.

[0051] Comparative Example 1

[0052] The comparative example uses foam warm mix asphalt concrete, and its raw material composition and preparation steps are basically the same as those of Example 1, except that in step S2 of the asphalt concrete preparation method of this comparative example, azodicarbonamide is directly used instead of a nano foaming agent.

[0053] Comparative Example 2

[0054] The comparative example uses foam warm mix asphalt concrete, and its raw material composition and preparation steps are basically the same as those of Example 1, except that in step S3 of the asphalt concrete preparation method of this comparative example, no organic viscosity-reducing warm mix additive is added to the raw materials.

[0055] The asphalt concrete samples prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to performance tests, and the performance results are shown in Table 1:

[0056] The compressive strength performance test method is tested according to ASTM D6107.

[0057] The stability performance test method refers to ASTM D1557 for load bearing ratio (CBR) test.

[0058] The durability performance test method refers to ASTM D4867 to evaluate the residual stability value of the water immersion Marshall test.

[0059] The rheological properties were tested by dynamic shear rheometer (DSR) according to ASTM D7175, which was specifically described by dynamic modulus and phase angle.

[0060] Table 1

[0061] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Compressive strength, MPa 8.2 7.9 8.1 6.5 8.8 Stability, kN 3.8 3.6 4.1 2.9 2.2 Durability, % 91 93 92 83 78 Dynamic modulus, MPa 1460 1370 1250 1520 1610 Phase angle, ° 15 14 15 17 26

[0062] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.

Claims

1. A method for preparing asphalt concrete using foam warm mix, characterized in that: The preparation method comprises the following steps: S1: Weigh the aggregate by weight and heat it, put the heated aggregate into the preheated mixing pot for dry mixing, and control the dry mixing temperature to 125-145°C; S2: heating the asphalt to 130-140°C, then injecting the nano foaming agent, stirring evenly and foaming for a period of time to obtain foamed asphalt; S3: spraying the foamed asphalt and the organic viscosity-reducing warm mix additive obtained in step S2 into the mixing pot of step S1 and mixing with the preheated aggregate; S4: Pause the mixing, pour in the room temperature mineral powder and water, and continue to mix until the mixture is uniform, thereby obtaining the asphalt concrete; The nano foaming agent is a nano molecular sieve loaded with azodicarbonamide, which is obtained by stirring and reacting the nano molecular sieve pretreated with acid solution with an alkaline solution of azodicarbonamide and then uniformly mixing with nano zinc oxide; the organic viscosity reducing warm mix additive is compounded with a hyperbranched polymer, polyvinyl pyrrolidone, fatty acid and amphoteric surfactant; the hyperbranched polymer is prepared by heating 2,4,6-tris(4-pyridine)-1,3,5-triazine and dibromoalkane in a solvent-free method, and using the active bromine atom of the dibromoalkane to replace the nitrogen atom on the pyridine ring of the triazine to generate a pyridinium salt.

2. The method for preparing asphalt concrete using foam warm mix as claimed in claim 1, characterized in that: The aggregate is composed of at least one coarse aggregate and at least one fine aggregate gradation.

3. The method for preparing asphalt concrete using foam warm mix as claimed in claim 1, characterized in that: In step S1, at least one fiber material selected from the group consisting of glass fiber, carbon fiber, basalt fiber and aramid fiber is added to the aggregate.

4. The method for preparing asphalt concrete using foam warm mix as claimed in claim 1, characterized in that: The dibromoalkane is at least one of 1,2-dibromoethane, 1,3-dibromopropane and 1,4-dibromobutane.

5. The method for preparing asphalt concrete using foam warm mix as claimed in claim 1, characterized in that: The fatty acid is at least one of lauric acid, myristic acid and oleic acid.

6. The method for preparing asphalt concrete using foam warm mix according to claim 1, characterized in that: The amphoteric surfactant is at least one of dodecyl dimethyl betaine, cocamidopropyl betaine, 2-lauryl-N-carboxymethyl-N-hydroxyethyl imidazoline and 2-alkyl-N-hydroxyethyl-N-hydroxypropyl sulfoimidazoline.

7. An asphalt concrete using foam warm mix, characterized in that: The asphalt concrete is prepared by the asphalt concrete preparation method using foam warm mix as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Foam mixture road structure and construction process thereof

    CN116377783A

  • Modified foaming agent and preparation method thereof

    CN1919901A